(untitled) (Indian Journal of Biochemistry and Biophysics (IJBB), 2023)
This study aims to analyze the AntiCovid effect of Phytocompounds extracted from Native Indian Plant species by computational methods such as Molecular Docking. Through this study keeping the Indian Heritage alive we characterized the ability of these phytochemicals as inhibiting agents of the Main Protease enzyme of this Virus. The lack of any effective treatment and the reoccurrence of cases despite Vaccination necessitates the quick provision of anti-SARS-CoV-2 drugs. Natural substances are getting a lot of attention for SARS-CoV-2 therapy as they have proven antimicrobial activities and are a key source for numerous antiviral drugs. Despite the fact that this virus has several identified target receptors, Main Protease (Mpro) is crucial for viral replication. In this study, 26 phytochemicals from 10 native Indian plant species were studied. Our docking studies demonstrated that compounds Quercetin, Withaferin A, Sominone, and Nimbin were likely to be more favorable than the natural inhibitor N3, with binding energies of−8.42, −9.21, −9.95, and −8.88 kcal/mol, respectively. These four candidate natural compounds were further examined for their bioavailability scoresthrough ADMET analysis to prove the safety of these compounds as well as their drug likeliness.Through the results it was indicated that these natural phytochemicals have a significant potential of inhibiting the SARS-CoV-2 Mpro enzyme and might be utilized to treat SARS-CoV-2 and manage public health, subject to in vitro validation in the future.